Peptidomimetic and Organometallic Derivatives of Primaquine Active against Leishmania infantum - Silvia Vale Costa (2012)
The current treatment of visceral leishmaniasis is made difficult by the low efficacy, elevated costs, low bioavailability, and high toxicity of many of the available drugs. Primaquine, an antimalarial 8-aminoquinoline, displays activity against Leishmania spp., and several of its derivatives have been developed as potential antileishmanial drugs. However, primaquine exhibits low oral bioavailability due to oxidative deamination of its aliphatic chain. We previously developed peptidomimetic and organometallic derivatives of primaquine, with higher resistance to proteolytic degradation and oxidative deamination, which presented significant activity against primaquine-sensitive pathogens such as Plasmodium or Pneumocystis. In light of these relevant findings, we decided to evaluate these compounds against both the promastigote and intramacrophagic amastigote forms of Leishmania infantum, the agent of Mediterranean visceral leishmaniasis. We found that several of these compounds had significant activity against L. infantum. One of the peptidomimetic (3c) and one of the organometallic (7a) derivatives of primaquine were active against the clinically relevant intramacrophagic amastigote form of the parasite, causing >96% reductions in the number of amastigotes per 100 macrophages at 60 and 40 mu M, respectively, while being less cytotoxic for host cells than the reference drugs sitamaquine and miltefosine. Hence, compounds 3c and 7a represent new entries toward the development of new antileishmanial leads.